Who can get the next Nobel Prize in infectious diseases? - Onder Ergonul; Can Ege Yalcin; Mahmut Alp Erkent; Mert Demirci; Sanem Pinar Uysal; Nur Zeynep Ay; Asena Omeroglu (International Journal of Infectious Diseases, 2016)
The aim of this paper is to deliver a perspective on future Nobel prizes by reviewing the features of Nobel prizes awarded in the infectious diseases-related (IDR) field over the last 115 years. Thirty-three out of 106 Nobel prizes (31%) in Physiology or Medicine have been awarded for IDR topics. Out of 58 Nobel laureates for IDR topics, two have been female; 67% have been medical doctors. The median age of Nobel laureates in Physiology or Medicine was found to be lower than the median age of laureates in Literature (p < 0.001). Since the Second World War, US-affiliated scientists have dominated the Nobel prizes (53%); however before 1945, German scientists did so (p = 0.005). The new antimicrobials received Nobel prizes until 1960; however no treatment study was awarded the Prize until the discovery of artemisinin and ivermectin, for which the Nobel Prize was awarded in 2015. Collaborative works have increasingly been appreciated. In the future, more female laureates would be expected in the IDR field. Medical graduates and scientists involved in multi-institutional and multidisciplinary collaborative efforts seem to have an advantage.